NOx Removal from Simulated Marine Exhaust Gas by Wet Scrubbing Using NaClO Solution - Zhitao Han; Bojun Liu; Shaolong Yang; Xinxiang Pan; Zhijun Yan (Journal of Chemistry)
The experiments were performed in a lab-scale countercurrent spraying reactor to study the NOx removal from simulated gas stream by cyclic scrubbing using NaClO solution. The effects of NaClO concentration, initial solution pH, coexisting gases (5% CO2 and 13% O2), NOx concentration, SO2 concentration, and absorbent temperature on NOx removal efficiency were investigated in regard to marine exhaust gas. When NaClO concentration was higher than 0.05 M and initial solution pH was below 8, NOx removal efficiency was relatively stable and it was higher than 60%. The coexisting CO2 (5%) had little effect on NOx removal efficiency, but the outlet CO2 concentration decreased slowly with the initial pH increasing from 6 to 8. A complete removal of SO2 and NO could be achieved simultaneously at 293 K, initial pH of 6, and NaClO concentration of 0.05 M, while the outlet NO2 concentration increased slightly with the increase of inlet SO2 concentration. NOx removal efficiency increased slightly with the increase of absorbent temperature. The relevant reaction mechanisms for the oxidation and absorption of NO with NaClO were also discussed. The results indicated that it was of great potential for NOx removal from marine exhaust gas by wet scrubbing using NaClO solution.